Biochemical characterization of blackberry fruit (Rubus sp) and jellies - de Souza, Angela Vacaro [UNESP]; Vieites, Rogério Lopes [UNESP]; Gomes, Estevão Perin [UNESP]; Vieira, Marcos Ribeiro da Silva (Southern Cross Publishing, 2018)
The present study aimed to quantify the phenolic compounds, carotenoids, anthocyanins and antioxidant activity using 2 different methods in blackberry fruits harvested at 3 different harvest points along the storage time and jellies made from these fruits and the quantification of ascorbic acid in the fruits. The harvesting points used were defined visually, being: 100% red (T1); 50% red and 50% black (T2) and 100% black (T3). After harvest, the fruits were selected, washed and packed in PET boxes with capacity for 200g of fruit and stored for 15 days at 2°C, being evaluated every 3 days and for the manufacture of the jellies, the fruits were first pulped in stainless steel pulping machine being the jellies prepared with 50:50 (fruit: commercial crystal sugar) in open pan. The results show that the loss of phenolic compounds, anthocyanins and carotenoids was small when fruits and jelly were compared, as well as the antioxidant activity, and this shows that the processing of this fruit does not cause losses in relation to these evaluated parameters.
Keywords: Anthocyanins; Flavonoids; Food processing; Harvesting point; Rubus sp